Profile of Argumentation of Grade 10th Students in Socioscientific Issues on Viruses Concept - Usmanah, Diva Islami; Fadlilah, Dina Rahma (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2025)
This study aims to determine the argumentation skills of grade 10th students towards socio-scientific issues at one of the senior high schools in Cileungsi, Bogor. This study was conducted using test and documentation techniques. The research method used is quantitative descriptive. Sampling was carried out using a purposive sampling technique; there are 128 students from 4 classes. The instruments used in this study were 5 standpoint questions related to the phenomenon of the spread of monkey pox and the test scores for virus material. The results of the study revealed that the quality of the written argumentation skills of class X students was mostly at levels 2 and 3, with an average percentage of 30.30% and 45.62% respectively. The findings imply that students are still in the process of developing higher-order thinking and scientific reasoning skills when engaging with socio-scientific issues. Therefore, science educators are encouraged to incorporate explicit argumentation-based learning strategies to promote deeper analysis, evidence-based reasoning, and the ability to construct coherent scientific arguments in response to real-world problems.